Evolution of the nursing method - Amparo Nogales Espert (Universidad de Alicante, 2012)
The present article tries to give a brief look down on the historic evolution of the nursing method to simply give evidence of the existence of a formal and continuous - never interrupted - education in nursing since long time ago, according to the different historic moments that nursing education suffered from higher or lower influence in society depending on the personalities implied at each time. As primary sources we have handled the Nursing Regulations of the Hospital Provincial de Valencia in 1897 in the custody of the Library Archives in the Diputación Provincial de Valencia. As a fundamental conclusion, we underline the paramount need to maintain a real service attitude to patients and society which are always basic to define and justify the existence of our profession.